2019
DOI: 10.3390/cells8080809
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cell PD-L1 Expression as Biomarker for Therapeutic Efficacy of Immune Checkpoint Inhibition in NSCLC

Abstract: Over the last decade, the immune checkpoint blockade targeting the programmed death protein 1 (PD-1)/programmed death ligand 1 (PD-L1) axis has improved progression-free and overall survival of advanced non-small cell lung cancer (NSCLC) patients. PD-L1 tumor expression, along with tumor mutational burden, is currently being explored as a predictive biomarker for responses to immune checkpoint inhibitors (ICIs). However, lung cancer patients may have insufficient tumor tissue samples and the high bleeding risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 47 publications
0
74
0
Order By: Relevance
“…Nevertheless, most of patients fail to respond to PD-1/PD-L1 axis inhibitors. The abnormal expression of PD-L1 can be used as a predictive or prognostic marker of PD-1/PD-L1 inhibition therapy for patients (31)(32)(33). However, few studies have studied the expression and regulatory mechanisms of PD-1 or PD-L1 expression in T-LBL (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, most of patients fail to respond to PD-1/PD-L1 axis inhibitors. The abnormal expression of PD-L1 can be used as a predictive or prognostic marker of PD-1/PD-L1 inhibition therapy for patients (31)(32)(33). However, few studies have studied the expression and regulatory mechanisms of PD-1 or PD-L1 expression in T-LBL (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the predictive value of PD-L1 IHC is still controversial, since in various types of cancer, including GC, some patients with PD-L1 negative tumors also respond to anti-PD-1 therapy [96,97]. Recently, Cheng et al [65] found that in GC patients with negative PD-L1 in tumor tissue, the CTC Imaging flow cytometry signal was as varied as that of IHC staining, suggesting that expression of CTC PD-L1 is useful in the immunophenotypic differential diagnosis of tumors and thus can be a potential candidate for anti-PD-1/PD-L1 immune checkpoint therapy [98]. CTC level after checkpoint blockade therapy may be effective to predict poor prognosis in advanced GC [99].…”
Section: The Role Of Ctcs In Gc Immunotherapymentioning
confidence: 99%
“…Other potential soluble biomarkers include TCR diversity and clonality [89,90], as well as circulating immune cell subsets such as the number MDSCs or different T cell phenotypes [91][92][93]. The is evolving data on the negative prognostic meaning of PD-L1+ circulating tumor cells (CTCs) in NSCLC [94,95], however, the clinical benefit of immune checkpoint blockade in NSCLC based on PD-L1 status of circulating tumor cells remains uncertain. The prognostic role of soluble forms of PD-1 and PD-L1 (sPD-1, sPD-L1) on peripheral blood is unclear.…”
Section: Circulating Markersmentioning
confidence: 99%